2016
DOI: 10.1155/2016/5081653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Culture Conditions to Obtain Fatty Acids from Saline Microalgae Species:Dunaliella salina,Sinecosyfissp., andChroomonassp.

Abstract: The use of the saline microalgae, Dunaliella salina, Sinecosyfis sp., and Chroomonas sp., was explored as an alternative source for the production of fatty acids using fertilizer and glycerol as culture media. The nutrient medium used contained “Nutrifoliar,” a commercial fertilizer, and/or glycerol, in natural sea water. The microalgae were placed in cultures with different conditions. The parameters that favored the largest production of fatty acids were 24 hours of agitation and illumination, 1620 L/day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Some saline strains present high percentages of omega oils that allow the exploration of obtaining, on a commercial scale, essential fatty acids such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA; Castilla‐Casadiego et al. ). The mycosporine‐like amino acids (MAAs) are known to absorb ultraviolet radiation (UVR) in the wavelength range 310–365 nm (Singh et al.…”
Section: Products and Applications Of Extremophile Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…Some saline strains present high percentages of omega oils that allow the exploration of obtaining, on a commercial scale, essential fatty acids such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA; Castilla‐Casadiego et al. ). The mycosporine‐like amino acids (MAAs) are known to absorb ultraviolet radiation (UVR) in the wavelength range 310–365 nm (Singh et al.…”
Section: Products and Applications Of Extremophile Microalgaementioning
confidence: 99%
“…Extremophiles microalgae, like Dunaliella bardawil, are often involved in carotenoids photoproduction thus gaining biotechnological relevance (Ben-Amotz et al 1988, Pick 1998, Fujiwara 2002, Podar and Reysenbach 2006, Garbayo et al 2008. Some saline strains present high percentages of omega oils that allow the exploration of obtaining, on a commercial scale, essential fatty acids such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA; Castilla-Casadiego et al 2016). The mycosporine-like amino acids (MAAs) are known to absorb ultraviolet radiation (UVR) in the wavelength range 310-365 nm (Singh et al 2010) and are found in wide range of microorganisms including cyanobacteria and eukaryotic algae (Singh and Gabani 2011).…”
Section: Microalgaementioning
confidence: 99%
“…Microalgae oils are an alternative, since they are the primary aquatic producers, capable of producing most of the nutrients needed for food produc-_________________ Corresponding editor: Mariel Gullian tion in the aquaculture industry (Shah et al 2018) . Fatty acids are accumulated by certain microalgal species, under specific culture conditions (Castilla-Casadiego et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the influence of abiotic stress on lipid and other metabolite concentrations. In most of them, fatty acids were reported only at one point of the stationary phase (Lamers et al 2012, Lee et al 2014, Castilla-Casadiego et al 2016, Hopkins et al 2019, Almutairi 2020, Chen et al 2020, Da Silva et al 2020, Hosseinzadeh-Gharajeh et al 2020a,b, Salinas-Whittaker et al 2020, Wu et al 2020. Microalgae cultured under optimal growth conditions principally synthesize fatty acids for membrane lipids (Hu et al 2008) but under unfavorable conditions, some accumulate energy in the form of neutral lipids (Singh et al 2016) .…”
Section: Introductionmentioning
confidence: 99%